THE IMPORTANCE OF SOCIAL INTELLIGENCE FOR ENTREPRENEURS TO IDENTIFY AND BUILD ON NEW MARKET OPPORTUNITIES IN THE ENGINEERING INDUSTRIES OF WESTERN MAHARASHTRA, INDIA (International Journal of Food and Nutritional Sciences, 2022)
Working social intelligence includes figuring out other people's feelings, thoughts, and behaviours. The western part of Maharashtra has historically been the epicentre of engineering industries due to the availability of natural resources and entrepreneurs' desire to make crucial investments. This study aims to understand the significance of social intelligence for entrepreneurs. Social intelligence is an essential part of various industries, and the way it is necessary for the engineering industries is the purpose of carrying out this research study in a country like India. Maharashtra is one of the highest revenue-generating states in India through its contributions in various sectors, and engineering industries are one of the most essential segments in the state's economy. Data collection is carried out through secondary sources, and analysis will be done through thematic analysis. Secondary data for this research has been collected from various secondary sources like online websites, government reports, websites of think tanks, and information provided by both the Government of India and the Government of Maharashtra. The data has been collected from the websites of the Government of India, like the Ministry of MSME, Ministry of Power, Ministry of Petroleum, Ministry of Coal, and Ministry of Commerce. Data from Maharashtra's Department of Industries government has also been taken along with the official websites of engineering industries like L & T, BHEL, and others. Thematic data analysis has been chosen, and this is due to the flexibility that it provides in bringing out a conclusion. Based on the research aims and objectives, themes have been prepared, and after making a consensus, all these themes have been analysed step by step.